2016
DOI: 10.3945/an.115.011635
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Grain Intake and Mortality from All Causes, Cardiovascular Disease, and Cancer: A Systematic Review and Dose-Response Meta-Analysis of Prospective Cohort Studies

Abstract: No conclusive information is available about the relation between the consumption of whole grains and the risk of mortality. We aimed to conduct a meta-analysis of prospective cohort studies to summarize the relation between whole-grain intake and risk of mortality from all causes, cardiovascular disease, and total and specific cancers. A systematic search of the literature published earlier than March 2015 was conducted in Medline and PubMed, SCOPUS, EMBASE, and Cochrane Library to identify relevant articles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 64 publications
0
63
0
11
Order By: Relevance
“…A metaanalysis of 18 prospective studies showed that higher whole grain intake was associated with a reduced risk of CHD (RR 0.79; 95% 0.74, 0.83) [88]. In a more recent analysis, Benisi-Kohansal et al showed that greater consumption of whole grains was associated with an 11% reduction in all-cause mortality (RR 0.89; 95% 0.84, 0.94), and a 16% reduction in CVD mortality (RR 0.84; 95% CI 0.76, 0.93) [89]. Similarly, Aune et al showed in a meta-analysis of prospective cohort studies that there was an inverse association between whole grain intake and CHD, CVD, and mortality from CHD, stroke and all-causes [90].…”
Section: Replacement Of Sfa With N-3 Pufamentioning
confidence: 99%
“…A metaanalysis of 18 prospective studies showed that higher whole grain intake was associated with a reduced risk of CHD (RR 0.79; 95% 0.74, 0.83) [88]. In a more recent analysis, Benisi-Kohansal et al showed that greater consumption of whole grains was associated with an 11% reduction in all-cause mortality (RR 0.89; 95% 0.84, 0.94), and a 16% reduction in CVD mortality (RR 0.84; 95% CI 0.76, 0.93) [89]. Similarly, Aune et al showed in a meta-analysis of prospective cohort studies that there was an inverse association between whole grain intake and CHD, CVD, and mortality from CHD, stroke and all-causes [90].…”
Section: Replacement Of Sfa With N-3 Pufamentioning
confidence: 99%
“…A large, recent systematic review and meta‐analysis of prospective cohort studies explored the relationship between wholegrain intake and risk of mortality from all causes, CVD, and total and specific cancers (Benisi Kohansal et al . ). In total, data from 2 282 603 participants from 20 studies were included.…”
Section: Why Should We Be Consuming Wholegrains?mentioning
confidence: 97%
“…Whilst all wholegrains contain fibre, the proportion and type of fibre in a wholegrain fluctuate greatly from one grain to the next (Kelloggs 2010). Wholegrains also provide other nutrients such as B vitamins, vitamin E, magnesium, zinc, iron, copper, selenium and other bioactive compounds (EUFIC 2015;BDA 2016;Benisi Kohansal et al 2016). It is this nutrient package that has been associated with the food groups' health promoting properties, and subsequently led to public health recommendations to consume more.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that report separate summary ratios for male and female will be combined using a fixed-effect model before being compiled in a random effects model as described in previous reviews (Benisi-Kohansal et al, 2016).…”
Section: Statistical Procedures and Conventionsmentioning
confidence: 99%
“…When the highest bound is open ended it will be assumed that it is the same as the adjacent interval. When the lower bound is open ended it will be assumed that it begins from 0 (Benisi- Kohansal et al, 2016). Statistical analysis will be conducted by two authors (G.S and W.I.)…”
Section: Statistical Procedures and Conventionsmentioning
confidence: 99%